New information on insect nematodes from Iran: report of Distolabrellus veechi (Nematoda: Mesorhabditidae) as new species and male of Oscheius tipulae (Nematoda: Rhabditidae) - Parissa Jalalinasab; Ramin Heydari; Reza Talaei-Hassanloui; Ebrahim Shokoohi; Javad Karimi (نامه انجمن حشره‌شناسی ایران)
In order to identify nematodes associated with insects in the forested areas of Guilan province, Iran, soil, wood, and insect samples were collected. Nematodes were extracted using the insect-baiting method, and the obtained specimens were analyzed based on both morphological and morphometric characteristics. This investigation led to the discovery populations belonging to the genera Distolabrellus and Oscheius, identified as D. veechi and O. tipulae, respectively. Molecular identification was carried out through molecular analysis, encompassing the D2-D3 expansion segment of 28S, ITS, and 18S genes of rRNA. The phylogenetic analyses placed these nematodes within their respective clades with high bootstrap support, confirming their identity. This survey marks the first discovery of D. veechi and male O. tipulae in Iran, introducing them as new records for the country.